Hedonic price analysis on urban housing : an empirical research on Hangzhou and Suzhou - Ho, Wendy Shu Ting (2013)
Housing prices have soared for the past decade in China, including second tier cities, like Hangzhou and Suzhou. Most studies compared and investigated on the determinants of housing prices across cities, with land price being the main determinant. While, most researchers have attempted to study the determinants of housing prices in first tier cities like Beijing and Shanghai, few studied on second tier cities. Hence, our paper aims to fill the gap for the lack of research on this area.